Borderline, stigmas and intervention perspectives: An integrative literature review (Research, Society and Development, 2024)
Borderline personality disorder (BPD) is characterized by emotional instability, impulsivity, difficulties in interpersonal relationships, and an unstable self-image. Although it shares characteristics with other psychiatric conditions, such as bipolar affective disorder (BAD), BPD can be differentiated by factors such as a history of early stress, traumatic experiences, and the emotional dysfunction resulting from these experiences. Accurate diagnosis is crucial for choosing an appropriate therapeutic intervention, and psychoneuroendocrine assessment can provide important insights, especially to differentiate BPD from other conditions with similar symptoms. Thus, this study aims to analyze Brazilian academic productions that address Borderline Personality Disorder. To this end, descriptive bibliographic research was used. The results show that psychoeducational interventions play a fundamental role in the treatment of BPD, promoting understanding of the disorder and reducing the stigma associated with the condition. Such approaches can improve emotional regulation and treatment adherence, in addition to strengthening family relationships. Dialectical Behavioral Therapy (DBT) stands out as an effective approach for managing BPD, helping to reduce impulsive behaviors and promote coping skills.